The health and well-being of older women living alone in the United Kingdom and beyond: a scoping review. (2nd January 2022) - Forward, Cat; Khan, H.T.A.; Fox, P.
ABSTRACT: In the United Kingdom (UK), women are more likely to live alone in later life. Social factors such as household composition have been shown to affect health and wellbeing as we age. The health and well-being of older women who live alone are of interest to researchers, care providers, health organizations, and policymakers. This article contributes to the literature by detailing a scoping review, establishing the current evidence in this field. The purpose and context of the review are given. The methodology and resulting data are described. Gaps in the literature and implications for practice and research are given.